A toolkit for genetics providers in follow‐up of patients with non‐diagnostic exome sequencing. Issue 2 (9th April 2019) - Zastrow, Diane B.; Kohler, Jennefer N.; Bonner, Devon; Reuter, Chloe M.; Fernandez, Liliana; Grove, Megan E.; Fisk, Dianna G.; ,; Yang, Yaping; Eng, Christine M.; Ward, Patricia A.; Bick, David; et al.
Abstract: There are approximately 7, 000 rare diseases affecting 25–30 million Americans, with 80% estimated to have a genetic basis. This presents a challenge for genetics practitioners to determine appropriate testing, make accurate diagnoses, and conduct up‐to‐date patient management. Exome sequencing (ES) is a comprehensive diagnostic approach, but only 25%–41% of the patients receive a molecular diagnosis. The remaining three‐fifths to three‐quarters of patients undergoing ES remain undiagnosed. The Stanford Center for Undiagnosed Diseases (CUD), a clinical site of the Undiagnosed Diseases Network, evaluates patients with undiagnosed and rare diseases using a combination of methods including ES. Frequently these patients have non‐diagnostic ES results, but strategic follow‐up techniques identify diagnoses in a subset. We present techniques used at the CUD that can be adopted by genetics providers in clinical follow‐up of cases where ES is non‐diagnostic. Solved case examples illustrate different types of non‐diagnostic results and the additional techniques that led to a diagnosis. Frequent approaches include segregation analysis, data reanalysis, genome sequencing, additional variant identification, careful phenotype‐disease correlation, confirmatory testing, and case matching. We also discuss prioritization of cases for additional analyses.